Tax preferences – a key component of the government regulation in Kazakhstan (Journal of Economic Research & Business Administration, 2016)
Legislative consolidation and application of privileges and preferences to the taxpayer is a stimulus of its development in every country. States put efforts in leading preferences or priorities on the need for the development of the industry, allowing to concentrate motivational activities to support the needs of a particular activity.In the Republic of Kazakhstan preferences mainly laid to peculiarities of the tax system. The preferential order of taxation uses following key guidelines:– The application of investment tax preferences; – The use of a special order of taxation on companies in special eco-nomic zones; – The application of special tax regimes for certain categories of tax-payers.
Keywords: preferences; taxes; government regulation; special eco-nomic zones; special tax conditions.